2008
DOI: 10.1038/mp.2008.102
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal dopamine transporter genotype with negative parenting: evidence for gene x environment interaction with child disruptive behavior

Abstract: Although maternal parenting is central to child development, little is known about the interplay between molecular genetic and environmental factors that influence parenting. We tested the association of the 40-bp variable number tandem repeat polymorphism of the dopamine transporter (DAT1; SLC6A3) gene with three dimensions of observed maternal parenting behavior (positive parenting, negative parenting and total maternal commands). A significant nonadditive association was found between maternal DAT1 genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 66 publications
4
48
0
Order By: Relevance
“…Yet, to the best of our knowledge, research on how parental genes moderate the influence of the child behavior on parenting is rare and has never included a sample of fathers (Kaitz et al., 2010; Lee et al., 2008; Morgan, Hammen, & Lee, 2016). Lee et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, to the best of our knowledge, research on how parental genes moderate the influence of the child behavior on parenting is rare and has never included a sample of fathers (Kaitz et al., 2010; Lee et al., 2008; Morgan, Hammen, & Lee, 2016). Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al. (2008), have found that mothers’ dopamine transporter genotype is associated with negative parenting. This association was significantly stronger among mothers whose children were highly disruptive.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, early maternal sensitivity has been positively associated with later aggressive responses, and early maternal depressive symptoms have been positively associated with children's negative attributions (Raikes and Thompson, 2008). Moreover, MC behavior appears to be tightly related with DA signaling in animals (Byrnes et al, 2002;Miller and Lonstein, 2005;Numan et al, 2005) and in humans (Lee et al, 2010), especially in dorsal and ventral striatal areas (Pruessner et al, 2004). All together, these data suggest that emotion processing, MC and DA signaling are strongly interconnected in modulating brain physiology.…”
Section: Introductionmentioning
confidence: 70%
“…The 10-repeat allele has been associated with greater levels of DAT expression (Heinz et al, 2000;Fuke et al, 2001;Mill et al, 2002;VanNess et al, 2005), although data in the opposite direction have also been reported (van Dyck et al, 2005). This polymorphism has also been associated with prefrontal and hippocampal activity during performance of cognitive tasks (Bertolino et al, 2006;Bertolino et al, 2008;Prata et al, 2009a;Prata et al, 2009b), with anxiety traits (Hunnerkopf et al, 2007) and with quality of parenting (Lee et al, 2010). More in detail, the DAT 3 0 VNTR 10 allele predicts greater scores for negative parenting in mothers when their offspring with ADHD symptoms present high child deviance (Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study by Lee et al (2010) have found a significant association between the presence of 9/10 genotype of maternal DAT1 gene with both negative parenting and children disruptive behaviour. Mothers with the 9/10 genotype had more difficulties in parenting,…”
Section: Dat Genotype-environment Interactionmentioning
confidence: 99%